Universal coverage and utilization of free long-lasting insecticidal nets for malaria prevention in Ghana: a cross-sectional study - Seth Kwaku Afagbedzi; Yakubu Alhassan; Ernest Kenu; Keziah Malm; Delia Akosua Benewaah Bandoh; Nana Yaw Peprah; Otubea Owusu Ansah; Chris Guure; Chris Guure (Frontiers Media S.A., 2023)
BackgroundMalaria continues to be one of the leading causes of mortality and morbidity, especially among children and pregnant women. The use of Long-Lasting Insecticide Nets (LLINs) has been recognized and prioritized as a major intervention for malaria prevention in Ghana. This study aims to establish the factors influencing the universal coverage and utilization of LLINs in Ghana.MethodsThe data used for this study was from a cross-sectional survey carried out to assess LLINs ownership and use in 9 out of the 10 old regions of Ghana from October 2018 to February 2019 where free LLIN distribution interventions were implemented. The EPI "30 × 7" cluster sampling method (three-stage sampling design) was modified to "15 × 14" and used for the study. A total of 9,977 households were interviewed from 42 districts. Descriptive statistics using percentages as well as tests of associations such as Pearson Chi-square and the magnitude of the associations using simple and multivariable logistic regression were implemented.ResultsOf the 9,977 households in the study, 88.0% of them owned at least one LLIN, universal coverage was 75.6%, while utilization was 65.6% among households with at least one LLIN. In the rural and urban areas, 90.8% and 83.2% of households, respectively, owned at least one LLIN. The was a 44% increase in universal coverage of LLINs in rural areas compared to urban areas (AOR: 1.44, 95% CI: 1.02-2.02). There were 29 higher odds of households being universally covered if they received LLIN from the PMD (AOR: 29.43, 95% CI: 24.21-35.79). Households with under-five children were 40% more likely to utilize LLIN (AOR: 1.40, 95% CI: 1.26-1.56). Respondents with universal coverage of LLIN had 25% increased odds of using nets (AOR: 1.25 95% CI: 1.06-1.48). Rural dwelling influences LLIN utilization, thus there was about 4-fold increase in household utilization of LLINs in rural areas compared to urban areas (AOR: 3.78, 95% CI: 2.73-5.24). Household size of more than 2 has high odds of LLINs utilization and awareness of the benefit of LLINs (AOR: 1.42, 95% CI: 1.18-1.71).ConclusionAbout nine in 10 households in Ghana have access at least to one LLIN, three-quarters had universal coverage, and over two-thirds of households with access used LLIN. The predictors of universal coverage included region of residence, rural dwellers, and PMD campaign, while households with child under-five, in rural areas, and with universal coverage were positively associated with utilization.